FIGURE 2A–E. Carbonea tephromelae. A in A new lichenicolous species of Carbonea (Ascomycota, Lecanoraceae) from northern Sweden - Svensson, Måns; Westberg, Martin (Zenodo, 2021)
FIGURE 2A–E. Carbonea tephromelae. A. Habitus - apothecia of C. tephromelae on the thallus of Tephromela atra (UPS L-994014, holotype). B. Section of an apothecium showing the colourless hypothecium, blue-green epihymenium and the dark excipulum (UPS L- 994013). C–E. Showing the range of ascospores shapes from globose to broadly ellipsoid (UPS L-119284). Scale bars: A=1 mm; B=100 µm; C–E=5 µm. : Published as part of Svensson, Måns & Westberg, Martin, 2021, A new lichenicolous species of Carbonea (Ascomycota, Lecanoraceae) from northern Sweden, pp. 221-230 in Phytotaxa 522 (3) on page 225, DOI: 10.11646/phytotaxa.522.3.5, http://zenodo.org/record/5560427